2019
DOI: 10.5001/omj.2019.40
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome Among Primary Care Physicians in Oman

Abstract: Objectives Medical professionals are exposed to many job stressors everyday, which can lead to psychological disturbances as well as burnout syndrome. We sought to assess the level of burnout among primary care physicians (PCPs) in Oman and explore risk factors for its development. Methods We conducted a cross-sectional, analytical study among a random cluster sample of 190 PCP working in Muscat, Oman. Indices of burnout (emotional exhaustion (EE), depersonalization (DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Due to these factors, PHC tends to exhibit high rates of turnover and those in the field are often prone to high risk of depressive disorders, poor job performance, and high rates of absenteeism (Al-Makhaita et al, 2014). In Oman, Al-Hashemi et al (2019) examined occupational burnout using the Maslach Burnout Inventory among PHCWs in an urban city of Oman, Muscat. This study reported a 6.3% prevalence of burnout and longer working hours was found to be strongly associated with the development of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these factors, PHC tends to exhibit high rates of turnover and those in the field are often prone to high risk of depressive disorders, poor job performance, and high rates of absenteeism (Al-Makhaita et al, 2014). In Oman, Al-Hashemi et al (2019) examined occupational burnout using the Maslach Burnout Inventory among PHCWs in an urban city of Oman, Muscat. This study reported a 6.3% prevalence of burnout and longer working hours was found to be strongly associated with the development of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study also reported that burnout was associated with being dissatisfied with work and intending to change jobs [58]. With regard to work environment, one study reported a weak association between workload and burnout while another showed more work hours to be associated with burnout [58,59]. One study looked at specific environmental factors and showed that disorganized patient flow to clinics, more paper work, and less cooperative colleagues were associated with high EE.…”
Section: Other Factors Associated With Burnoutmentioning
confidence: 97%
“…There were seven studies addressing physicians in primary health care (PHC) [53][54][55][56][57][58][59]. These studies came from five countries: KSA; UAE; Qatar; Oman and Kuwait.…”
Section: Practicing Physiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, urbanization and dependence on the modern cash economy have become a rule rather than an exception. Amid such changes, there is growing evidence to suggest that occupational stress or burnout once reported in industrialized countries are increasingly becoming common in many such societies in transition [ 2 ]. The Chinese sage, Confucius, who lived in the 6th century, is credited to have said: "choose a job you love, and you will never have to work a day in your life”.…”
Section: Introductionmentioning
confidence: 99%